C-Band Polarimetric Coherences and Ratios for Discriminating Sea Ice Roughness. (22nd May 2013) - Gupta, Mukesh; Scharien, Randall K.; Barber, David G.
Abstract : The rapid decline of sea ice in the Arctic has resulted in a variable sea ice roughness that necessitates improved methods for efficient observation using high-resolution spaceborne radar. The utility of C-band polarimetric backscatter, coherences, and ratios as a discriminator of ice surface roughness is evaluated. An existing one-dimensional backscatter model has been modified to two-dimensions (2D) by considering deviation in the orientation (i.e., the slopes) in azimuth and range direction of surface roughness simultaneously as an improvement in the model. It is shown theoretically that the circular coherence (ρ RRLL ) decreases exponentially with increasing surface roughness. The crosspolarized coherence (ρ HHVH ) is found to be less sensitive to surface roughness, whereas the copolarized coherence (ρ VVHH ) decreases at far-range incidence angles for all ice types. A complete validation of the adapted 2D model using direct measurements of surface roughness is suggested as an avenue for further research.